A spell for change - Jarvis, Nicole (Titan Books, 2025)
"Kate Mayer has always been troubled by visions of the future. No matter what she does, her disturbing premonitions come to pass--often with terrible consequences. But Kate has a secret: swirling, romantic dreams of a strange boy, and a chance meeting in the woods. Oliver Chadwick Jr. returned from the Great War disabled, disillusioned, and able to see the dead. Haunted by the death of his best friend, Oliver realizes that his ability to communicate with spirits may offer the chance of closure he desperately seeks. Nora Jo Barker's mother and grandmother were witches, but she has never nurtured her own power. Always an outsider, she has made a place for herself as the town's schoolteacher, clinging to the independence the job affords her. When her unorthodox ideas lead to her dismissal, salvation comes in the form of a witch from the mountains, who offers her a magical apprenticeship. Yet as she begins to fall for another woman in town, her loyalties pull her in disparate directions. Rumors of a dark force stalking the town only push Kate, Oliver, and Nora Jo onwards in their quest to determine their own destinies. But there are powers in the world stronger and stranger than their own, and not all magic is used for good..."--